Race and America's Immigrant Press How the Slovaks were Taught to Think Like White People - Zecker, Robert M. (Bloomsbury Academic, 2011)
Race was all over the immigrant newspaper week after week. As early as the 1890s the papers of the largest Slovak fraternal societies covered lynchings in the South. While somewhat sympathetic, these articles nevertheless enabled immigrants to distance themselves from the "blackness" of victims, and became part of a strategy of asserting newcomers' tentative claims to "whiteness." Southern and eastern European immigrants began to think of themselves as white people. They asserted their place in the U.S. and demanded the right to be regarded as "Caucasians," with all the privileges that accompanied this designation. Immigrant newspapers offered a stunning array of lynching accounts, poems and cartoons mocking blacks, and paeans to America's imperial adventures in the Caribbean and Asia. Immigrants themselves had a far greater role to play in their own racial identity formation than has so far been acknowledged.